2012
DOI: 10.1143/apex.5.112501
|View full text |Cite
|
Sign up to set email alerts
|

At-Wavelength Extreme Ultraviolet Lithography Mask Observation Using a High-Magnification Objective with Three Multilayer Mirrors

Abstract: Motivated by the need for at-wavelength observation of extreme ultraviolet (EUV) lithography masks, we developed a full-field EUV microscope that has a multilayer-mirror objective. This objective is based on an innovative optical design that gives a magnification of over ×1400, enabling us to use a conventional charge-coupled device (CCD) camera as the detector. In addition, when the objective is corrected for off-axis aberrations, it has a large field of view of a few hundred micrometers, permitting rapid ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…The fluctuations are not mask defect. 22) In a previous paper, we reported that the hp 225 and 88 nm L/S without the residual-type defects were clearly resolved with the image contrasts of 0.64 and 0.52, respectively. 22) The impacts of the residual-type defect on the EUV reflectivity were calculated from the captured images.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…The fluctuations are not mask defect. 22) In a previous paper, we reported that the hp 225 and 88 nm L/S without the residual-type defects were clearly resolved with the image contrasts of 0.64 and 0.52, respectively. 22) The impacts of the residual-type defect on the EUV reflectivity were calculated from the captured images.…”
mentioning
confidence: 79%
“…17) Therefore, this study focuses on the effects of various thicknesses of the residual-type defects on printed features by employing the EUV microscope as a mask pattern inspection tool. [18][19][20][21][22] This is because in inspecting narrow mask patterns such as half-pitch (hp) 88 nm lines and spaces (L/S) it is difficult to obtain excellent image contrast and analyze the multilayer damage using an inspection tool which employs deep ultraviolet light. 5) While it is true that in atomic force microscopy (AFM) the image quality is affected by cantilever tip quality, this technique has the potential in inspecting pattern sizes as small as hp 88 nm L/S.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These fluctuations are not mask defect. 27 However, the captured images clearly indicate the intensity loss of the EUV light from the space pattern due to the presence of the phase defects. In these cases, the locations of the phase defects were defined as 56, 88, and 160 nm in position.…”
Section: Observation Of the Phase Defects Using Euv Microscopementioning
confidence: 97%
“…EUV microscopes have been long developed to observe circuit pattern images at actual exposure wavelength, that is, under EUV light . There are also microscopes that make possible observation at the same conditions as in exposure machines .…”
Section: Introductionmentioning
confidence: 99%